Standardization of a technology for virgin coconut oil - ANOOP A DEEPIKA S.V JAISY JOSEPH; Dr. V Ganesan (Guide) (Tavanur 2010 Kelappaji College of Agricultural Engineering and Technology)
Standardization of a technology for virgin coconut oil
Standardization of a technology for virgin coconut oil